The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.clinmicnews.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Meningitis

Abstract: Infectious meningitis is a large public health concern, especially in children and immunocompromised patients. Although the epidemiology of meningitis has shown significant decline in past decades, partly due to the introduction of vaccines, outbreaks are still reported worldwide. Diagnosis of meningitis is of critical importance, and it is considered to be one of the most urgent of the microbiological medical emergencies. In order to improve the treatment strategy, various diagnostic methods have been develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In the present study, only 20 cases of osteoarticular involvement were reported over 15 years review, which concurs with other previous surveys [ 6 , 8 ]. The reason behind the low-rate involvement of osteoarticular tissue in melioidosis might be attributed to the low blood supply to these locations comparing to other organs and, in parallel, the fact that the majority of melioidosis cases are bacteremic and affect mostly organs rich with blood supply such as liver, spleen, lungs and brain [ 34 , 35 ]. In another study performed in tropical Australia, the percentages of primary and secondary melioidotic septic arthritis among 536 confirmed cases were 2.4 % and 2.6 %, respectively [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, only 20 cases of osteoarticular involvement were reported over 15 years review, which concurs with other previous surveys [ 6 , 8 ]. The reason behind the low-rate involvement of osteoarticular tissue in melioidosis might be attributed to the low blood supply to these locations comparing to other organs and, in parallel, the fact that the majority of melioidosis cases are bacteremic and affect mostly organs rich with blood supply such as liver, spleen, lungs and brain [ 34 , 35 ]. In another study performed in tropical Australia, the percentages of primary and secondary melioidotic septic arthritis among 536 confirmed cases were 2.4 % and 2.6 %, respectively [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Meningitis may instigate necrosis, reduced CSF and blood flow, and malfunctioning of central nervous system (CNS)(Zueter and Zaiter 2015 ). Meningitis might be outcome of either infectious or non-infectious sources (Barani et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Infectious meningitis is a severe CNS disorder which, as a result of microbial infection, causes inflammation of the meninges. Usually, this is induced through viruses and bacteria and occasionally via parasites and fungi (Zueter and Zaiter 2015 ). The viral infection in CNS produces inflammation in separate anatomical regions such as the meninges, brain parenchyma, and cranial nerves or in various areas at the same time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations